2020
DOI: 10.7150/jca.46329
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress for the Techniques of MRI-Guided Breast Interventions and their applications on Surgical Strategy

Abstract: With a high sensitivity of breast lesions, MRI can detect suspicious lesions which are occult in traditional breast examination equipment. However, the lower and variable specificity of MRI makes the MRI-guided intervention, including biopsies and localizations, necessary before surgery, especially for patients who need the treatment of breast-conserving surgery (BCS). MRI techniques and patient preparation should be first carefully considered before the intervention to avoid lengthening the procedure time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 100 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…However, both surgeons and patients hope to have a more accurate MRI assessment of lesions like US and x-ray in clinical practice. Maltez (27,36). Brennan et al (37) found that severe and moderate BPE may lead to a higher cancellation rate of MRI biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…However, both surgeons and patients hope to have a more accurate MRI assessment of lesions like US and x-ray in clinical practice. Maltez (27,36). Brennan et al (37) found that severe and moderate BPE may lead to a higher cancellation rate of MRI biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…While the sensitivity is high, the specificity is not satisfactory, resulting from the fact that normal breast tissue or benign lesions show enhancement on MRI. Therefore, suspicious lesions found on MRI are subjected to mammography or ultrasound in order to confirm their presence and then imaging guided localization or biopsy procedure is performed [16]. However, using the three-dimensional information about lesion location from MRI requires knowledge and experience in both techniques, including the ability to process the data pertaining to the lesion position from one modality to another.…”
Section: Discussionmentioning
confidence: 99%
“…Forward kinematics [9][10][11][12] derives the spatial position and posture of the end motion point relative to the basic coordinate system from the driving angle or displacement of each joint. By solving forward kinematics, the workspace of the mechanism can be obtained, and whether the designed mechanism meets the design requirements can be detected.…”
Section: Forward Kinematics Analysismentioning
confidence: 99%